2018
DOI: 10.1016/j.seizure.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends and population differences in the incidence of epilepsy. A population-based study from Saskatchewan, Canada

Abstract: The incidence of epilepsy in Saskatchewan, Canada was comparable to previous incidence studies from developed countries. This study is the first Canadian study calculating the secular trends and all-age group incidence of epilepsy and one of the few studies showing the incidence of epilepsy in a self-declared Registered Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
3
7
0
Order By: Relevance
“…The treatment process and timeline for adults with NOE are clinically different. As it is, the lapsed time for epilepsy surgery for adults in Saskatchewan is almost 20 years, similar to other centers which were 22.1 years (29,35). Given that the definition of DRE utilizes a timeline of 2 years, there should be a much more rapid referral to tertiary epilepsy surgical centers in both our province and globally.…”
Section: Percentage Of Dre By Year Of Follow-upsupporting
confidence: 53%
See 2 more Smart Citations
“…The treatment process and timeline for adults with NOE are clinically different. As it is, the lapsed time for epilepsy surgery for adults in Saskatchewan is almost 20 years, similar to other centers which were 22.1 years (29,35). Given that the definition of DRE utilizes a timeline of 2 years, there should be a much more rapid referral to tertiary epilepsy surgical centers in both our province and globally.…”
Section: Percentage Of Dre By Year Of Follow-upsupporting
confidence: 53%
“…For this reason, we chose not to include ethnicity, or indigenous ancestry, as a risk factor in this study. This is a significant limitation given recent publications in Canada showing that indigenous persons are at 2 times the risk for developing epilepsy ( 36 ). It would then be reasonable to assume that it should be included as a risk factor for the progression of the condition as well, along with other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A recent study from the adjacent Canadian province of Saskatchewan found that the incidence of epilepsy in the Indigenous population is double the national average. 5 , 9 , 10 , 29 Although ethnicity data were not available on chart review, there is no reason to assume that Indigenous persons do not comprise a similar majority of SE medical evacuations. Recurrent minor seizures (and by extension, epilepsy) in this population may be under‐reported due to understandable enduring mistrust of the healthcare system resulting from extreme historical inequities, 30 stigma against seizures, or cultural interpretation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the composition of the steering group was heterogenous in terms of ethnicity, gender, age, and location in order to represent a range of perspectives, many minority and marginalized groups, as well as those aged under 18 and over 70, were underrepresented in the survey results, and thus the final list of priorities may not fully reflect the views of the diverse Canadian population. Clinical best practices, availability of diagnostic testing, and access to specialists can vary widely across the country, and systematic inequities exist on a regional scale, particularly in the Arctic territories and among Indigenous populations [37].…”
Section: Limitationsmentioning
confidence: 99%